2019
DOI: 10.1371/journal.pone.0225375
|View full text |Cite
|
Sign up to set email alerts
|

A single plasmid based CRISPR interference in Synechocystis 6803 – A proof of concept

Abstract: We developed a simple method to apply CRISPR interference by modifying an existing plasmid pCRISPathBrick containing the native S. pyogenes CRISPR assembly for Synechocystis PCC6803 and named it pCRPB1010. The technique presented here using deadCas9 is easier to implement for gene silencing in Synechocystis PCC6803 than other existing techniques as it circumvents the genome integration and segregation steps thereby significantly shortens the construction of the mutant strains. We executed CRISPR interference a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…As mentioned by Yao et al [17], the blocking of transcription elongation may not be as efficient if the gene of interest is part of an operon with a distant TSS. Nevertheless, the repression levels obtained in this study are within those previously reported for other targets in Synechocystis [17,26,27]. On the one hand, it is also possible to purposefully design the sgRNA further from the TSS, resulting in lower repression of the target gene(s) and enabling fine-tuning gene expression, as demonstrated by Shabestary et al [26].…”
Section: Repression Of Three Kpsm Homologues In Synechocystis and Characterization Of The 3-sgrna Mutantsupporting
confidence: 84%
“…As mentioned by Yao et al [17], the blocking of transcription elongation may not be as efficient if the gene of interest is part of an operon with a distant TSS. Nevertheless, the repression levels obtained in this study are within those previously reported for other targets in Synechocystis [17,26,27]. On the one hand, it is also possible to purposefully design the sgRNA further from the TSS, resulting in lower repression of the target gene(s) and enabling fine-tuning gene expression, as demonstrated by Shabestary et al [26].…”
Section: Repression Of Three Kpsm Homologues In Synechocystis and Characterization Of The 3-sgrna Mutantsupporting
confidence: 84%
“…In one example of this type of strategy, DNase-dead Cpf1 was introduced into S. elongatus UTEX 2973 as part of a CRISPRi system to target Photosystem I for inhibition [ 128 ]. Additionally, a plasmid-based CRISPRi system was introduced into S6803 [ 129 ] to inhibit the expression of the D1 protein of photosystem II, and Liu et al [ 130 ] introduced a reversible CRISPRi system into S6803 by using a Rhamnose-theophylline inducible promoter system. This CRISPRi system was able to almost completely knock out PSII by targeting the D2 ( psbD gene) protein, and it was fully reversible.…”
Section: Use Of Crispr and Crispr Interference For Study Of Photosynt...mentioning
confidence: 99%
“…Escherichia coli strain DH5α was used for routine DNA manipulations [ 21 ] and constructions in Luria broth (LB) medium at 37°C [ 22 ]…”
Section: Methodsmentioning
confidence: 99%